Common Grasses of Meerut - Singh, V. (Indian Forester, 1971)
This study deals with the common grasses of Meerut with particular reference to an area of about 15 km in radius with Meerut College as the centre. A total of 82 species representing 50 genera have been listed from this area. Of these 26 genera and 44 species belong to the Panicoideae and 24 genera and 38 species to the Pooideae. The Panicoideae is represented by all the three tribes, while the Poodeae by only 14 tribes.